SEPARATION OF ANTIOXIDANT COMPOUNDS FROM THE STEM BARK EXTRACTS OF HAEMATOSTAPHIS BARTERI HOOK F. (ANACARDIACEAE) USING CHROMATOGRAPHIC TECHNIQUES - Ezekiel, S. J.; Adamu, H. M.; Chindo, I. Y.; Garba, I. H.; Tadzabia, K. (FUDMA JOURNAL OF SCIENCES, 2023)
In the search for plants with antioxidant properties, Haematostaphis barteri Hook f. (Anacardiaceae) was found to be a plant often used in Nigeria and other nations for the management of cancer, anemia, haemorrhoid and many other ailments. The ethyl acetate and acetone extracts of the stem bark in previous research by the same author were assayed for phenolic compounds and the phenolic compounds were found to possess antioxidant properties when TLC chromatograms were stained with iodine vapour and several spots were revealed. The ethyl acetate and acetone fractions were further chromatographed on TLC with several solvent systems and the mixtures from toluene, ethyl acetate and formic acid (TEF) in the ratio of 4/2.5/3.5 and 3/5/2 and n-butanol, acetic acid and water (BAW) in the ratio of 12/4/6 gave better resolutions. When chromatograms were obtained and developed with a solution of p-anisaldehyde in concentrated sulphuric acid, different spots were visualizedwith different colours signifying the presence of different bioactive metabolites. The Presence of antioxidant compounds was determined by bioutography TLC chromatograms were stained with a solution of 0.2% DPPH (2, 2-Diphenyl-1-picrylhydrazyl) solution in methanol and dried with heat gun and the appearance of yellow spots on purple background signifies the presence of antioxidants. A selected spot with an Rf value of 0.31 was monitored and isolated from column chromatography. The purified bioactive metabolite was crystallized, weighed and saved for further analysis.
Keywords: cancer; ethyl acetate extract; chromatography; bioautography